Delayed Spontaneous Rupture of a Posterior Inferior Cerebellar Artery Aneurysm Following Treatment with Flow Diversion: A Clinicopathologic Study - Chow, M.; McDougall, C.; O'Kelly, C.; Ashforth, R.; Johnson, E.; Fiorella, D. (American Journal of Neuroradiology, 2012)
SUMMARY: In this report, we present the fatal spontaneous delayed rupture of a previously unruptured large PICA aneurysm following treatment with the PED. Pathology at postmortem examination has supported the theory that intra-aneurysmal thrombus may acutely destabilize the aneurysm wall. Aneurysms with an anatomic arrangement that promote continued flow into the neck may not be optimal candidates for the flow-diversion treatment strategy. AAAabdominal aortic aneurysmASanterior spinal arteryBbasilarHEhematoxylin-eosinILTintraluminal thrombusLAICleft anterior inferior cerebellar arteryLVleft vertebral arteryMmedullaMRAMR angiographyPponsPEDPipeline Embolization DevicePICAposterior inferior cerebellar arterypO2partial pressure of oxygenPODpostoperative dayRPICright posterior inferior cerebellar arteryRVright vertebral artery